(3fXQjJG GdbGfhf hGdMb hJWHjbGJgeG aj GdbhGfjf GdLRGFQjI (B/s - (3efUhQ, GSMGb EHQGgjes ((3GdLRGFQ (B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2007)
(3jVe GdfXQjI GdYGeI ddbGfhf hJWHjbGJgG aj GdbhGfjf GdLRGFQjI, GdJYQja HGdbGfhf hHjGf NUGFUg, JbSjeGJ GdbGfhf hEfhGY GdbhGYO GdbGfhfjI, GdCUhd GdadSajI ddbhGfjf hecGfI GdbGfhf GdLRGFQj, eUGOQ GdbGfhf, eLGd JWHjb GdbhGfjf, JaSjQ GdbhGfjf, GdfXQjI GdYGeI ddMb hJWHjbGJgG aj GdbhGfjf GdLRGFQjI, GdMb hCQcGfg, CfhGY GdMbhb, eUGOQ GdMbhb, EKHGJ GdMb, RhGd GdMb(B.s
(3HjHdjhZQGajG(B: (3U U(B.367-368s
Keywords: (3GdMbs; (3GdbGfhfs; (3fXQjI GdMbs